A quick Chan–Lam C–N and C–S cross coupling at room temperature in the presence of square pyramidal [Cu(DMAP)4I]I as a catalyst. Issue 6 (24th November 2015) - Roy, Subhasish; Sarma, Manas Jyoti; Kashyap, Bishwapran; Phukan, Prodeep
Abstract : A rapid and efficient protocol for C–N and C–S cross coupling has been developed using a new square pyramidal copper complex, [Cu(DMAP)4 I]I. Abstract : A rapid and efficient protocol for C–N and C–S cross coupling has been developed using a new square pyramidal copper complex, [Cu(DMAP)4 I]I. The complex was successfully synthesized via a disproportionation reaction of CuI and DMAP in DMSO. The catalytic activity of the complex was found to be excellent for Chan–Lam coupling reaction between aryl boronic acid and amine, amide, azide or thiol. The reaction could be carried out in the presence of only 2 mol% of the copper catalyst in methanol at room temperature within a short time.